Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Pamekasan Yang Dimediasi Pengembangan Karir - Sri Mulyani; Chamariyah Chamariyah; M. Alfin Nour (Journal of Management and Creative Business, 2024)
Alfin Nour, 2023. The influence of organizational culture on the performance of Pamekasan Regency Population and Civil Registration Office employees mediated by Career Development, Postgraduate Program at Wijaya Putra University. This type of research is explanatory, the research approach used is quantitative, the research sample is 47 respondents. Data analysis using SPSS and PLS analysis. The aims of this study were: 1) To analyze the effect of organizational culture on the performance of the Pamekasan Regency Population and Civil Registration Office employees; 2) To analyze the influence of organizational culture on the career development of Pamekasan Regency Population and Civil Registration Office employees; 3) To analyze the effect of career development on the performance of the Pamekasan Regency Population and Civil Registration Office employees; 4) To analyze the indirect effect of organizational culture on the performance of the Pamekasan Regency Population and Civil Registration Office employees mediated by career development. The results showed that: 1) Organizational culture has a significant effect on the performance of the Pamekasan Regency Population and Civil Registration Office employees with an original sample value of 0.338; 2) Organizational culture has a significant influence on the career development of employees of the Pamekasan Regency Population and Civil Registration Service with an original sample value of 0.547; 3) Career development has a significant effect on employee performance with an original sample value of 0.593; 4) Organizational culture has a significant indirect effect on the performance of employees of the Pamekasan Regency Population and Civil Registration Service which is mediated by career development with an original sample value of 0.324 and a p-value of 0.000.